Leprosy in Refugees and Migrants in Italy and a Literature Review of Cases Reported in Europe between 2009 and 2018 - Anna Beltrame; Gianfranco Barabino; Yiran Wei; Andrea Clapasson; Pierantonio Orza; Francesca Perandin; Chiara Piubelli; Geraldo Badona Monteiro; Silvia Stefania Longoni; Paola Rodari; Silvia Duranti; Ronaldo Silva; et al. (Microorganisms, 2020)
Leprosy is a chronic neglected infectious disease that affects over 200,000 people each year and causes disabilities in more than four million people in Asia, Africa, and Latin America. The disease can appear with a wide spectrum of clinical forms, and therefore the clinical suspicion is often difficult. Refugees and migrants from endemic countries affected by leprosy can remain undiagnosed in Europe due to the unpreparedness of clinicians. We retrospectively describe the characteristics of 55 refugees/migrants with a diagnosis of leprosy established in Italy from 2009 to 2018. Continents of origin were Africa (42%), Asia (40%), and South and Central America (18%). The symptoms reported were skin lesions (91%), neuropathy (71%), edema (7%), eye involvement (6%), fever (6%), arthritis (4%), and lymphadenopathy (4%). Seven patients (13%) had irreversible complications. Overall, 35% were relapses and 66% multibacillary leprosy. Furthermore, we conducted a review of 17 case reports or case series and five nationwide reports, published in the same decade, describing 280 migrant patients with leprosy in Europe. In Europe, leprosy is a rare chronic infectious disease, but it has not completely disappeared. Diagnosis and treatment of leprosy in refugees and migrants from endemic countries are a challenge. European guidelines for this neglected disease in this high-risk population would be beneficial.